Synthesis, structural characterisation, and preliminary evaluation of non-indolin-2-one-based angiogenesis inhibitors related to sunitinib (Sutent®) - Pichit Sudta (2018)
The indolin-2-one fused-ring system and the 2,4-dimethylpyrrole unit represent key structural motifs in the anticancer drug sunitinib (Sutent®) and predecessor angiogenesis inhibitors that have undergone anticancer clinical trials (e.g. semaxanib, SU5416). In pursuit of novel anti-angiogenic scaffolds, we were interested in identifying whether the indolin-2-one group in these structures could be modified without losing activity. This paper describes novel condensation chemistry used to prepare a test series of (E)-and (Z)-alkenes related to SU5416 that retain the 2,4-dimethylpyrrole unit while incorporating ring-opened indolin-2-ones. Unique structural characteristics were identified in the compounds, such as intramolecular hydrogen bonds in the (Z)-alkenes, and several examples were shown to possess significant anti-angiogenic activity in a rat aorta in vitro model of angiogenesis. The work demonstrates that the indolin-2-one moiety is not an absolute requirement for angiogenesis inhibition in the sunitinib/SU5416 class. © 2013 CSIRO.